Metal Oxides-Based Semiconductors for Biosensors Applications - Şerban, Ionel; Enesca, Alexandru (Frontiers in Chemistry, 2020)
The present mini-review contains a concessive overview on the recent achievement regarding the implementation of metal oxide semiconductor in biosensors used in biological and environmental systems. The paper explores the pathway of enhancing the sensing characteristics of metal oxides by optimizing various parameters such as synthesis methods, morphology, composition and structure. Four representative metal oxides (TiO2, ZnO, SnO2 and WO3) are presented based on several aspects: synthesis method, morphology, functionalizing molecules, detection target and limit of detection (LOD).